(untitled) (Informatica, 2019)
In this paper, we present Refin-Align a new refinement algorithm for a multiple sequence alignment. Refining alignment consists on constructing a new more accurate multiple sequence alignment from an initial one by applying some modifications. Our refinement algorithm Refin-Align uses a new definition of block and also our multiple sequence alignment algorithm Pro-malign. We assess our algorithm Refin-Align on multiple sequence alignment constructed by different algorithms using different benchmarks of protein sequences. In the most cases treated, our algorithm improves the scores of the multiple sequence alignment.